Tinnitus characteristics in patients with idiopathic sudden sensorineural hearing loss and acute tinnitus - Mohammad Mokhatrish; Wonyong Baek; Gi‐Sung Nam; Sung Il Cho (Laryngoscope Investigative Otolaryngology, 2023)
Abstract Objective Tinnitus is a common symptom of idiopathic sudden sensorineural hearing loss (ISSHL). This study aimed to investigate the characteristics and outcomes of acute tinnitus in patients with ISSHL. Methods A total of 59 patients with ISSHL and acute tinnitus were enrolled. All patients underwent audiological assessment, tinnitus matching for loudness and frequency, and steroid treatment for sudden hearing loss. Tinnitus‐related distress was assessed using the tinnitus handicap inventory (THI) questionnaire. The outcomes of hearing recovery and tinnitus remission were investigated retrospectively. Results The loudness and pitch of acute tinnitus were 63.2 ± 22.4 dB HL and 2010.63 ± 2368.99 Hz, respectively. Complete and partial recovery rates of acute tinnitus in ISSHL patients were 32.2% and 39% according to the THI scores. The group with complete recovery of hearing showed significantly greater improvement in tinnitus distress than the group with no improvement in hearing. The loudness and pitch of tinnitus did not correlate with tinnitus remission. Conclusion Hearing recovery is more important for tinnitus remission than the psychoacoustic characteristics of acute tinnitus. Timely identification and proper treatment of hearing loss are important to improve tinnitus remission in patients with ISSHL. Level of Evidence Level 4.